MRI and FDG PET/CT Findings for Borderline Brenner Tumor of the Ovary: A Case Report and Literature Review - Hiroki Matsutani; Go Nakai; Takashi Yamada; Kazuhiro Yamamoto; Masahide Ohmichi; Keigo Osuga (Case Reports in Obstetrics and Gynecology)
The imaging features of borderline Brenner tumor (BT) of the ovary are very limited, especially regarding apparent diffusion coefficient (ADC) value and 18F-fluorodeoxyglucose positron emission tomography (FDG-PET)/CT. We report a case of borderline BT in a 54-year-old woman with diffusion-weighted imaging (DWI) and FDG-PET/CT findings. Furthermore, ADC values and maximum standardized uptake value (SUV max) in the present case were compared with those of an additional 7 cases of benign BT in this institution in addition to literature reviews. Magnetic resonance imaging (MRI) revealed a pelvic unilocular cystic tumor with two solid components. The solid mass showing a low signal intensity (SI) in T2-weighted images (T2WI) and DWI was diagnosed as a benign BT histologically. The papillary tumor adjacent to the solid mass showing intermediate SI in T2WIs and high SI on DWI was a borderline BT. The mean ADC value (×10-3 mm2/s) of benign BTs (n=7) and benign component in this case (n=1) was 1.13, and the range of ADC values was broad (0.51–1.8). While, the ADC value of borderline Brenner component in this case was 1.10. The mean SUVmax of the benign BTs (n=4) demonstrated mild FDG uptakes (2.3, range 1.9–2.6) in contrast with moderate FDG uptake (SUVmax: 5.8) of borderline Brenner component in this case and high FDG uptake (SUVmax: 9.6) of a malignant BT in a previous report. ADC values for the solid component of BTs are not useful for differentiating benign from malignant or borderline components, whereas PET/CT could be useful.